KEYLESS USER DEFINED OPTIMAL SECURITY ENCRYPTION (International Journal of Engineering and Computer Science, 2013)
Cryptography and encryptions, these terms are now-a-days have an unseen impact in the merging field of network and its security. In the global communal world, where faster access to precise information is the most basic need; security of confidential data during transfer from one place to another place is a major concern. There are a lot of sheltered approaches that can be applied inside the organizations premises to keep the data safe and sound. The prime goal leading the design of an encryption algorithm must provide security against unauthorized attacks. Key-oriented algorithms are very efficient but they were very bulky to manage as key handling must be done. Due to the great overhead, keyless algorithms seem an attractive option. There can be various techniques that can be used to attain secure transfer of data like firewalls, proxy servers, and steganography, data security plans against worms, viruses or denial-of-service attacks